Data Linkage: Cleft Live-Birth Prevalence and Hospitalizations in Western Australia: 1980 to 2016. (October 2020) - Nicholls, Wendy; Harper, Craig; Robinson, Suzanne
Objective: To provide information on live-birth prevalence and hospitalizations, including anxiety and depression, for cleft lip and/or palate (CL/P) in Western Australia (WA), using live-birth data 1980 to 2015. Design: Retrospective data linkage. Setting: Tertiary hospital. Patients: Cleft cohort consisted of people live-born with CL/P in WA between 1980 and 2015, and a gender and age-matched control group. Measures: Live-birth prevalence for CL/P by year. Hospital event counts, event ages, and length of stay (LOS) days by 18 diagnosis groups and 4 birth year categories between the cleft cohort and control group, and between cleft types. Count of events per alive persons per calendar year, and relative risk for proportions of persons in the cleft cohort and control group by diagnosis group. Results: Live-birth prevalence for CL/P was 19.7 per 10 000 (1 in 522). The cleft cohort had significantly higher event counts, lower event ages, and higher LOS days than the control group. Cleft lip and palate had significantly higher event counts, lower event ages, and higher LOS days than cleft lip or cleft palate only. There were 2 significant differences for anxiety or depression between the cleft cohort and control group, lower event ages, and higher LOS days in 1990s birth year category. Conclusions: This study provides a cleft data reference for WA. Live-birth prevalence for all clefts and by cleft type offers an appropriate method for estimating service utilization and provision. Patients with cleft accessed hospital services more frequently, at an earlier age, with higher LOS days than the control group.